The impact of the quality of health services on the loyalty of health insurance clients in the state of Jazeera-Sudan - Alsheekh, Amani Abdelatti Omer; Ali, Muhsin Mohammed Gasmalla (Journal of Economic, Administrative and Legal Sciences, 2023)
The study aimed to find out the impact of the quality of health services in its dimensions of (tangibility, attention, safety, response) on the loyalty of customers in the health insurance sector in the state of Gezira – Sudan. The problem of the study was the observation of the researchers deteriorating the health sector in Sudan in light of the economic conditions experienced by the country, which has an impact on the quality of health services provided in the health insurance sector and thus on the satisfaction and loyalty of customers of this sector. The importance of the study was to bridge the research gap in this field and provide results for decision makers, based on previous literature. The study model and its hypotheses were formed represented in the impact of the dimensions of service quality (tangibility, responsiveness, attention, safety) on the degree of customer loyalty. The study also relied on the descriptive analytical method, and the questionnaire was used as a tool to collect study data from a sample of (138) singles. To test the hypotheses, descriptive and inferential statistics methods were used depending on the (SPSS) program, and the results of the study showed a significant impact of the dimensions of the quality of health services on customer loyalty, and the lack of availability of dimensions of quality of services in the health insurance sector in the state of Gezira.
Keywords: quality; quality of service; customer loyalty; responsiveness; attention; safety; tangibility